2021
DOI: 10.1186/s12913-021-07000-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of universal home visits on child health in Bauchi State, Nigeria: a stepped wedge cluster randomised controlled trial

Abstract: Background Nigeria is the second biggest contributor to global child mortality. Infectious diseases continue to be major killers. In Bauchi State, Nigeria, a stepped wedge cluster randomised controlled trial tested the health impacts of universal home visits to pregnant women and their spouses. We present here the findings related to early child health. Methods The home visits took place in eight wards in Toro Local Government Authority, randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…This is a recognised feature of the most significant change technique [61] and authors have recommended confirmation of reported benefits by other means [62]. In our case, we confirmed the impact of the home visits on knowledge, views and health outcomes using quantitative methods in the context of a cluster randomised controlled trial [31][32][33]. The changes described in the stories are likely to be context-specific and may not apply in other settings, but the approach of sharing evidence to allow households to take preventive actions is more widely relevant.…”
Section: Limitationssupporting
confidence: 83%
See 2 more Smart Citations
“…This is a recognised feature of the most significant change technique [61] and authors have recommended confirmation of reported benefits by other means [62]. In our case, we confirmed the impact of the home visits on knowledge, views and health outcomes using quantitative methods in the context of a cluster randomised controlled trial [31][32][33]. The changes described in the stories are likely to be context-specific and may not apply in other settings, but the approach of sharing evidence to allow households to take preventive actions is more widely relevant.…”
Section: Limitationssupporting
confidence: 83%
“…Taken together with the quantitative evidence of impact of the home visits on maternal and child health outcomes [31][32][33], the narratives of change described here reinforce the idea that home visits to share evidence with pregnant women and their spouses can empower households to take action to improve their own situation. The Bauchi State Primary Health Care Development Agency has already committed to extending such home visits throughout the State, as funding permits.…”
Section: Policy Implicationssupporting
confidence: 53%
See 1 more Smart Citation
“…Less than half the included studies were randomised controlled trials, and study outcomes did not include maternal and child health indicators. Our trial showed an impact of the home visits on men’s knowledge and attitudes, as well as improvements in both maternal and child health outcomes [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent stepped wedge cluster randomized controlled trial of home visits to pregnant women and their spouses in Bauchi State, Nigeria [ 14 ] reported large and significant impacts on maternal health outcomes [ 15 ] and on child health outcomes [ 16 ]. The visits targeted upstream actionable risk factors for maternal health, based on the findings from a previous survey in the state [ 17 ].…”
mentioning
confidence: 99%